Establishment of a novel therapeutic vector targeting the trigeminal ganglion in rats - Xu K; Pan SY; Song JX; ,Liu XN; An N; Zheng X (Dove Medical Press, 2016)
Kun Xu,1,2 Shi-Yin Pan,1,2 Jin-Xin Song,1 Xian-Ning Liu,1,2 Na An,1,2 Xuan Zheng1,2 1Department of Ophthalmology, The No 1 Hospital of Xi’an, 2Shaanxi Provincial Key Laboratory of Ophthalmology, Ophthalmological Institute of Shaanxi Province, Xi’an, Shaanxi Province, People’s Republic of China Background: In the pathogenesis of herpes simplex keratitis, herpes simplex virus type 1 (HSV-1) infection begins in corneal epithelium cells and then progresses through the sensory nerve endings and finally travels up forward to the trigeminal ganglion (TG), where it remains as latent virus. The available anti-HSV therapies do not completely suppress the recurrence of active HSV-1 infection. The aim of this study was to establish a novel replication-defective (rd) HSV-1 (rdHSV) vector (rdHSV-interferon gamma [IFNγ]) that could effectively target the TG. Methods: Recombinant HSV-1 virus was inserted into a shuttle plasmid carrying IFNγ to establish the rdHSV-IFNγ vector. Safety was evaluated in vitro by 50% cellular cytotoxicity in transfected SH-SY5Y neuroblastoma cells and in vivo by Kaplan–Meier survival estimate and infection rate. Wistar rats were immunized with rdHSV-IFNγ to evaluate the TG targeting efficiency. Real-time polymerase chain reaction and Western blot assays were used to evaluate IFNγ mRNA and protein expression and rdHSV-IFNγ localization. Results: The rdHSV-IFNγ vector was successfully constructed and showed high in vitro safety and overall survival and a corneal infection rate similar to that of control rats immunized with saline (control group; P>0.05). Real-time polymerase chain reaction and immunohistochemistry assays confirmed IFNγ expression and effective TG targeting on days 14 and 21, which increased with postimmunization time. Moreover, IFNγ was expressed sufficiently in the TG tissues. Conclusion: The rdHSV-IFNγ can act as an effective gene transporting vector that carries the therapeutic genes to the TG and triggers its expression. Keywords: replication-defective HSV-1, interferon gamma, trigeminal ganglion, therapeutic gene